The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1556/018.68.2017.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Salinity tolerance of grafted watermelon seedlings

Abstract: In order to evaluate the salinity tolerance of grafted watermelon, two sets of experiments were conducted in a growing chamber where 'Esmeralda' varieties were grafted onto interspecific squash (Cucurbita maxima Duch. × Cucurbita moschata Duch.) and Lagenaria siceraria rootstocks. Both non-grafted and self-garfted plants were used for control. For salt stress, 2.85 and 4.28 mM/l substrate doses of NaCl were added with each irrigation in 2 day intervals for a duration of 23 days. Interspecific-grafted plants sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…This effect was more influential in the ungrafted plants when compared to the grafted plants. It was reported by Böhm et al (2017) that the highest tolerance against salt stress was seen in grafted plants with watermelon, with an improvement observed in the plant biomass and leaf area, not a reduction, due to salinity. Colla et al (2010) observed increased dry weight values and a greater number of leaves in all of the grafted watermelon plants in their study when compared to the ungrafted control group, and it was stated by Penella et al (2016) that a reduction in the leaf area of ungrafted plants was observed when they were grown under stress, and this condition did not change in any of the combinations of grafted pepper plants.…”
Section: Discussionmentioning
confidence: 92%
“…This effect was more influential in the ungrafted plants when compared to the grafted plants. It was reported by Böhm et al (2017) that the highest tolerance against salt stress was seen in grafted plants with watermelon, with an improvement observed in the plant biomass and leaf area, not a reduction, due to salinity. Colla et al (2010) observed increased dry weight values and a greater number of leaves in all of the grafted watermelon plants in their study when compared to the ungrafted control group, and it was stated by Penella et al (2016) that a reduction in the leaf area of ungrafted plants was observed when they were grown under stress, and this condition did not change in any of the combinations of grafted pepper plants.…”
Section: Discussionmentioning
confidence: 92%
“…Commonly, grafting is considered a tool to boost the vegetative growth of scion cultivars, especially under adverse soil conditions ( Colla et al., 2010a ; Colla et al., 2010b ; Schwarz et al., 2013 ; Böhm et al., 2017 ). Yet, in our experiment, the influence of scion on the rootstocks seems to be the opposite as compared with self-grafted C. maxima × C. moschata (CC) or L. siceraria (Ls), and DM plant values of graft combinations of melon and watermelon with Ls and CC were significantly lower.…”
Section: Discussionmentioning
confidence: 99%
“…The Na + and Cl − concentration in leaves, roots, and fruits tissues was evaluated using an ICP-OES spectrometer (IRIS Thermo Jarrel ASH Corp., Franklin, MA, USA). The homogenous plants samples were used for these analyses [40].…”
Section: Determination Of Na + and CL − In Roots Leaves And Fruitsmentioning
confidence: 99%